SURGICAL REMOVAL OF THE FIBROSIS AND GRAFTING WITH SAPHENOUS VEIN IN TREATING PEYRONIE DISEASE: TWO CASE REPORTS (Vietnam Journal of Community Medicine, 2022)
Treatment of La Peyronie by plaque incision and by saphenous vein graft is a surgicalmethod to lengthen the tunica albuginea. This method is currently one of the best methods totreat La Peyronie. Open surgery to take the saphenous vein graft is still the popular method.However, by advances in endoscopic surgery, endoscopic saphenous vein graft is applied.Report of 2 clinical cases: A 68-year-old male patient was diagnosed with La Peyronie.He had difficulty in sexual intercourse for 3 years. The size of the cavernous sclerosis massin the middle of the dorsal penis is 3x2 cm. The surgery takes 150 minutes. The patientwas hospitalized for 7 days. The urinary catheter is kept for 1 day. The femoral drainageis withdrawn after 6 days. During the hospital stay, there were no haemorrhage and noinfection complications.A 54-year-old man has a fibrous mass in the middle of the ventral surface of the penis.The size of the fibrous mass is 2 x 1.5 cm. The surgery takes 120 minutes. The patientwas hospitalized for 7 days. The urinary catheter is kept for 1 day. The femoral drainageis withdrawn after 6 days. During the hospital stay, there were no haemorrhage and noinfection complications. The patient had edema of the right thigh. After treated with antiinflammatory therapy, the patient was stabilized.Conclusion: The surgical reconstruction using the saphenous vein graft to treat La Peyronieis a safe surgical method with the high treatment efficiency. Endoscopic saphenous veingraft is an effective method to take the saphenous vein.
Keywords: Case report, Peyronie disease, removing the fibrosis, grafting with saphenous vein.